The atrial appendage as a suitable source to generate cardiac‐derived adherent proliferating cells for regenerative cell‐based therapies. (21st November 2017) - Detert, Stephan; Stamm, Christof; Beez, Christien; Diedrichs, Falk; Ringe, Jochen; Van Linthout, Sophie; Seifert, Martina; Tschöpe, Carsten; Sittinger, Michael; Haag, Marion
Abstract: Cardiac‐derived adherent proliferating (CardAP) cells obtained from endomyocardial biopsies (EMBs) with known anti‐fibrotic and pro‐angiogenic properties are good candidates for the autologous therapy of end‐stage cardiac diseases such as dilated cardiomyopathy. However, due to the limited number of CardAP cells that can be obtained from EMBs, our aim is to isolate cells with similar properties from other regions of the heart with comparable tissue architecture. Here, we introduce the atrial appendage as a candidate region. Atrial appendage‐derived cells were sorted with CD90 microbeads to obtain a CD90 low cell population, which were subsequently analysed for their surface marker and gene expression profiles via flow cytometry and micro array analysis. Enzyme‐linked immunosorbent assays for vascular endothelial growth factor and interleukin‐8 as well as tube formation assays were performed to investigate pro‐angiogenic properties. Furthermore, growth kinetic assays were performed to estimate the cell numbers needed for cell‐based products. Microarray analysis revealed the expression of numerous pro‐angiogenic genes and strong similarities to CardAP cells with which they also share expression levels of defined surface antigens, that is, CD29 +, CD44 +, CD45 −, CD73 +, CD90 low, CD105 +, and CD166 + . High secretion levels of vascular endothelial growth factor and interleukin‐8 as well as improved properties of vascular structures in vitro could be detected. Based on growth parameters, cell dosages for the treatment of more than 250 patients are possible using one appendage. These results lead to the conclusion that isolating cells with regenerative characteristics from atrial appendages is feasible and permits further investigations towards allogenic cell‐based therapies.